Chain end-termination of p-polybenzimidazole by bulk segment for efficient electrochemical power generation and hydrogen separation - Seo, Kwangwon; Nam, Ki-Ho; Han, Haksoo (Journal of industrial and engineering chemistry (Seoul, Korea), 2020)
[Display omitted] We investigated the effects of hydrogen separation using high-temperature anhydrous proton-exchange membrane fuel-cell technology. Various acid-doped para-polybenzimidazole (p-PBI)-chain end-tethered amine-polyhedral oligomeric silsesquioxane (NH2-POSS) membranes were prepared via a unique sol–gel transition method termed as the poly(phosphoric acid) process. The resulting NH2-POSS-capped p-PBI membranes exhibited a higher phosphoric acid-doping level (128–223.5%) and proton conductivity (0.23–0.29Scm−1 at 160°C and 0% relative humidity) than the parent p-PBI membrane. The chemical chain end-termination of p-PBI with cage-like NH2-POSS significantly enhanced the electrochemical H2/CO2 and H2/CO separation at 160°C. The hydrogen separation of the NH2-POSS-capped p-PBI system required a relatively small amount of energy, and the system exhibited a good dynamic response. The favorable interfacial interaction between the NH2-POSS and the p-PBI host, high thermomechanical stability, and good fuel-cell and hydrogen-separation performance at high temperatures up to 160°C indicate the applicability of the NH2-POSS-capped p-PBI membranes to electrochemical power generation and hydrogen pumps for practical industrial applications in harsh and extreme environments.